Pengaruh Perhatian Guru Pendidikan Agama Kristen Terhadap Minat Belajar Siswa Kelas VIII SMP N 4 Siborongborong Tahun Pembelajaran 2023/2024 - Tiurma Ulina Manik; Damayanti Nababan; Lasmaria Lumban Tobing; Tianggur M Napitupulu; Maria Widiastuti (Sinar Kasih: Jurnal Pendidikan Agama dan Filsafat, 2023)
The aim of this research is to determine the positive and significant influence between the attention of Christian religious education teachers on the learning interest of class VIII students at SMP N 4 Siborongborong for the 2023/2024 academic year. The research method used is a quantitative research method. The population was 206 students in class VIII of SMP N 4 Siborongborong for the 2023/2024 academic year and a sample of 52 people was determined using random sampling techniques. Data was collected using a positive closed questionnaire with 32 items, namely 16 items for variable 2024: 1) Test the analysis requirements: a) positive relationship test obtained rxy = 0.550 > rtable(a=0.05,n=52) = 0.297. b) Testing a significant relationship obtained a value of tcount= 4.651 > ttable(a=0.05, dk=n-2=50)= 2.000. 2) Test the effect: a) Test the regression equation, obtained the regression equation Y ̂="27.20"+0.48X. b) Regression coefficient of determination test (r2) = 30.2%. 3) Test the hypothesis using the F test to obtain Fcount > Ftable=(a=0.05, dk numerator k=22, dk denominator=n-2=52-2=50) namely 21.63 > 1.39. Thus Ha is accepted and H0 is rejected.